Diversity analyses in two ornamental and large-genome Ranunculaceae species based on a low-cost Klenow NGS-based protocol - Martina, Matteo; Acquadro, Alberto; Portis, Ezio; Barchi, Lorenzo; Lanteri, Sergio (Frontiers in Plant Science, 2023)
Persian buttercup (Ranunculus asiaticus L.) and poppy anemone (Anemone coronaria L.) are ornamental, outcrossing, perennial species belonging to the Ranunculaceae family, characterized by large and highly repetitive genomes. We applied K-seq protocol in both species to generate high-throughput sequencing data and produce a large number of genetic polymorphisms. The technique entails the application of Klenow polymerase-based PCR using short primers designed by analyzing k-mer sets in the genome sequence. To date the genome sequence of both species has not been released, thus we designed primer sets based on the reference the genome sequence of the related species Aquilegia oxysepala var. kansuensis (Brühl). A whole of 11,542 SNPs were selected for assessing genetic diversity of eighteen commercial varieties of R. asiaticus, while 1,752 SNPs for assessing genetic diversity in six cultivars of A. coronaria. UPGMA dendrograms were constructed and in R. asiaticus integrated in with PCA analysis. This study reports the first molecular fingerprinting within Persian buttercup, while the results obtained in poppy anemone were compared with a previously published SSR-based fingerprinting, proving K-seq to be an efficient protocol for the genotyping of complex genetic backgrounds.